Targeting oncogenic activation of FLT3/SREBP/FASN promotes the therapeutic effect of quizartinib involving disruption of mitochondrial phospholipids - Feng Yin; Jing Yang; Hao Luo; Tiantian Yu; Wenhua Lu; Mingyue Zhao; Hongli Du; Shijun Wen; Peng Huang; Yumin Hu (Cell Death and Disease)
Abstract FMS-like tyrosine kinase 3–internal tandem duplication (FLT3/ITD) is a common driver mutation that presents with a high leukemic burden and its impact on metabolic homeostasis remains to be further investigated. Here, we revealed that the oncogenic activation of FLT3/ITD induced upregulation of target genes of sterol regulatory element-binding proteins (SREBPs) in vivo and in acute myeloid leukemia patients. Quizartinib is a second-generation FLT3 inhibitor that selectively inhibits the activating FLT3 mutations. We demonstrated the critical role of SREBP1 degradation in conferring the response of FLT3/ITD cells to quizartinib. Mechanistically, quizartinib facilitated degradation of the precursor form of SREBP1 via the FLT3/AKT/GSK3 axis and reduced protein levels of its target gene fatty acid synthase (FASN). Lipidomics analysis by Liquid Chromatography Mass Spectrometry (LC-MS) demonstrated that inhibition of FLT3 altered global levels of phospholipids including reduction of cardiolipin, leading to subsequent loss of mitochondrial membrane potential. Pharmacological inhibition of SREBP1 or FASN sensitized FLT3/ITD leukemia cells to quizartinib. Quizartinib combined with SREBP inhibitor fatostatin or FASN inhibitor orlistat provided substantial therapeutic benefit over monotherapies in the murine FLT3/ITD leukemia model. Our results indicated the mechanistic link between FLT3/ITD and SREBP degradation and suggested the combination therapy via targeting FLT3/SREBP/FASN axis.